Sukuk: A Veritable Tool for Effective Waqf Fund Management in Nigeria - Umar, Adamu; Aliyu, Shehu (Ekonomi Syariah IAIN Kudus, 2019)
Since its emergence in the early 2000’s, Sukuk has been regarded as the most significant innovation recorded in the Islamic capital market. Sukuk is generally regarded as an equivalent of conventional bond, Sukuk paved way for mobilization of long term Shari’ah compliant funds for equally Shari’ah compliant undertakings. Islamic capital market experts have developed various Shari’ah compliant Sukuk structures, notable among which is Waqf-based Sukuk structure. Viewed as a distinct ethical capitalism and a veritable vehicle for long term financing, Waqf was found to record tremendous impact in all spares of human needs. The paper seeks to unveil how Waqf-based Sukuk could be used to attain effective mobilization as well as management of Waqf assets. It explores the possibility of issuing Waqf-based Sukuk for the development, renovation, reconstruction and modification of Waqf assets in Nigeria. The paper employs a non-experimental, deductive-analytical approach, in its investigation. Evidences show that Waqf-linked Sukuk has been successful in the development of Waqf assets in countries like Indonesia, Singapore and Saudi Arabia. Accordingly, the paper develops a Waqf-based Sukuk (ijarah) framework for fund mobilization for development of Waqf properties in Nigeria. We strongly recommend that both formal and non-formal Waqf institutions in Nigeria should utilize this outlet to effectively develop, deepen and manage their philanthropic activities.